Analysis of the Impact of Business Activity Components in the Agricultural Sector as a Strategy to Improve Rice Farming Profitability: A Study in Lempuing District, Ogan Komering Ilir Regency, South Sumatra - Waluyo Tri Purtanto; Kamaruzzaman Onaning (ESENSI: Jurnal Manajemen Bisnis, 2024)
The fairly large demand for rice is not supported by the attraction of farming. The government's role in helping farming by providing subsidies for subsidized fertilizer amounting to around IDR 33 trillion each year or around IDR 330 trillion in the last 10 years has had no impact on agricultural productivity. Research using quantitative methods in Lempuing District, Ogan Komering Ulu Regency, South Sumatra Province with a sample size of 200 respondents carried out identification and evaluation using the 5M management element approach, namely Money which is represented by the ability to provide land area, Materials (seeds, Fertilizers and Pepticides), Man, review labor requirements, Machine is the use of machinery or agricultural machinery equipment and Method is a method of implementing the frequency of rice planting in one year. The results of research using the Structural Equation Model method with the help of the SmartPLS application program provide the conclusion that: 1. Utilization of modernization of agricultural machinery (Machine) as the main priority in increasing profitability. Modern machines have a positive effect and replace the role of labor (Man) which has a negative effect because agricultural labor is less attractive and has high costs. Assistance with the availability of modern machine equipment is the main solution for areas that have not received it. 2. Land area (Money) is also vital in farming, because a proportional land area will have an impact on profitability and efficiency in material costs and machine rental utilization. Ownership of land area for agricultural use in accordance with the average per capita household expenditure needs is a minimum of 1.75 Ha for those who have their own land and 3.16 Ha for rice farming using a land rental system.